If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -14.5 = x Reorder the terms: -14.5 + 6x = x Solving -14.5 + 6x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -14.5 + 6x + -1x = x + -1x Combine like terms: 6x + -1x = 5x -14.5 + 5x = x + -1x Combine like terms: x + -1x = 0 -14.5 + 5x = 0 Add '14.5' to each side of the equation. -14.5 + 14.5 + 5x = 0 + 14.5 Combine like terms: -14.5 + 14.5 = 0.0 0.0 + 5x = 0 + 14.5 5x = 0 + 14.5 Combine like terms: 0 + 14.5 = 14.5 5x = 14.5 Divide each side by '5'. x = 2.9 Simplifying x = 2.9
| 10x^2/20x^2-25x | | 5p(2)-245=0 | | 0.3x+0.1=-0.8 | | -3x-43=2(x+2)+8 | | -5x-13=-28 | | 3w-2(4-8w)=8w+25 | | z^2-z+0.25=0 | | 9=-7-3-a+a | | (9y+11)(4y+5)=0 | | 423/16-281/4 | | 5x+38=4(2x+2) | | 6(5-4v)=2(4v-17) | | -3x+20=23 | | 2(4x+3)+1=2x+49 | | -6x/6 | | -2x-20=3(x+1)-8 | | 2(x+4)=x+3 | | 9x+3y=5 | | 8x^2+42x+49=0 | | 8x-4=4x-40 | | 8(4u-7)-8u=-2(u+2) | | 2x+2/6x^2+16x+10 | | -7x-6=-4x-24 | | a(2)-7a+6=0 | | 144w^2-9=0 | | x^2+xy-x=3 | | Y=6x^2+17x-28 | | (1/2)x+9=10 | | 6n(2)+36n+54=0 | | 4(2x-3)+4x=6(2x+5) | | 24x^2+48-72=0 | | 5-3x+4(x-3)=4 |